(untitled) (Research, Society and Development, 2023)
Objectives: To analyze the impacts of gram negative batteries on the appearance of hematological complications during the postoperative period. Methods: Articles, theses and dissertations, files made available in scientific journals from 2015 onwards were prioritized, with files in the mother tongue and in the foreign language English being chosen. The research platforms where the articles were searched were: Scielo, National Library of Medicine National Institutes of Health (PubMed), Science Direct through the descriptors “Gram-Negative Bacteria” AND “Blood Circulation” AND “Postoperative Complications.Results: The study had a sample of 4 articles. it was possible to show that post-appendectomy complications due to gram-negative microorganisms are not rare. All articles mostly cited the relationship between complications related to gram-negative bacteria and the empirical use of antimicrobials in the perioperative period and bacterial resistance Conclusion: The choice of antibiotics for complicated appendicitis must address local patterns of antibiotic resistance, a Intraoperative culture in cases of complicated appendicitis appears to facilitate the selection of appropriate postoperative antibiotics and thus minimize SSIs and overall morbidity.